Aplikasi Pengelolaan Tagihan Pembeli pada CV Apolindo Jaya Semesta Menggunakan Metode RUP - Serenity Devina Suryanto; Dina Lestari Putri; Novan Wijaya (MDP Student Conference, 2026)
This project aims to develop a buyer bill management application at CV Apolindo Jaya Semesta in Mobile form in order to overcome the shortcomings and problems of manual management methods and help companies manage buyer bills quickly and efficiently. This project focuses on project initialization, designing user interface designs and UML Use Case diagrams, and testing with the Black Box Testing method and users who use the application are admins and company leaders. The method used is the Rational Unified Process (RUP) which organizes the project iteratively and gradually. The results of this project development show that this application is proven to be able to solve the company's problems and shortcomings with a test result rate of 100%, can solve 90% of manual problems, save time by 70%, and costs up to 60%, although there are still opportunities for further development in the aspect of expanding features and application coverage.